Phthalic acid esters in the marine environment - Corcoran, Eugene F. (1978)
The waters, particulate matter and sediments of the lower Mississippi River and the adjacent Gulf of Mexico were examined for their concentrations of phthalic acid ester plasticizers and nutrients. The nutrient content of the water remained almost constant in the river, but decreased rapidly upon entrance into the Gulf of Mexico. The phthalic acid ester concentrations, on the other hand, gradually increased from New Orleans downriver to Head of the Passes. But like the nutrients their concentrations also decreased rapidly into the Gulf of Mexico. The predominant phthalic acid ester (PAE) was di- (2-ethyl hexyl) phthalate, a plasticizer commonly used in resins and synthetic rubber. The cumulative concentration of the PAE's was from 1-2 ppb with the greatest concentration in the water. Particulate matter has about half the concentration, while the PAE's were almost absent in the sediment. Laboratory experiments have indicated that there is a great loss of phthalie acid ester due to hydrolytic activity. This may possibly explain the lowm concentration in the sediments.